2012
DOI: 10.1038/nm.2596
|View full text |Cite
|
Sign up to set email alerts
|

A tumor suppressor function of Smurf2 associated with controlling chromatin landscape and genome stability through RNF20

Abstract: In addition to allelic mutations, cancers are known to harbor alterations in their chromatin landscape. Here, we show that genomic ablation of Smurf2, a HECT-domain E3 ubiquitin ligase, results in dysregulation of DNA damage response and genomic stability, culminating to increased susceptibility to various types of cancers in aged mice. We demonstrate that Smurf2 regulates histone H2B monoubiquitination as well as histone H3 tri-methylation at K4 and K79 by targeting RNF20 to proteasomal degradation in both mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(174 citation statements)
references
References 45 publications
(57 reference statements)
5
167
0
2
Order By: Relevance
“…In so much as the defect in HRR is able to trigger sufficient genomic instability to accelerate cancer-promoting mutations (Cousineau and Belmaaza, 2007), the dysfunctional SUPT16H pathway could conceivably increase cancer susceptibility. Consistent with this prediction, recent studies have shown that tumorigenesis is promoted by dysfunction of Smurf2, a HECT-domain E3 ubiquitin ligase, which induces RNF20 degradation by proteasomal machinery (Blank et al, 2012). Similarly, CDC73, which regulates H2B ubiquitylation through its interaction with RNF20, is mutated and/or downregulated in various types of tumors (Hahn et al, 2012).…”
Section: C922smentioning
confidence: 73%
“…In so much as the defect in HRR is able to trigger sufficient genomic instability to accelerate cancer-promoting mutations (Cousineau and Belmaaza, 2007), the dysfunctional SUPT16H pathway could conceivably increase cancer susceptibility. Consistent with this prediction, recent studies have shown that tumorigenesis is promoted by dysfunction of Smurf2, a HECT-domain E3 ubiquitin ligase, which induces RNF20 degradation by proteasomal machinery (Blank et al, 2012). Similarly, CDC73, which regulates H2B ubiquitylation through its interaction with RNF20, is mutated and/or downregulated in various types of tumors (Hahn et al, 2012).…”
Section: C922smentioning
confidence: 73%
“…Further studies in HCT116 cells and nude mice suggested that the autoneddylation of Smurf1 and the ubiquitin ligase activity of Smurf1 were critical for its tumour-promoting function. In contrast to the tumourpromoting role of Smurf1, Smurf2 has been suggested to function as a tumour suppressor gene since ablation of Smurf2 in mice resulted in increased susceptibility to various types of cancers in aged mice 61 . We noted that the NAE inhibitor MLN4924 has been recently identified as a novel approach to the treatment of acute myeloid leukaemia, head and neck cancer and liver cancer [62][63][64] .…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant H2Bub1 levels can affect development (Wright et al 2011), apoptosis (Walter et al 2010), stem cell differentiation (Buszczak et al 2009;Fuchs et al 2012;Karpiuk et al 2012), viral infection outcome (Sarkari et al 2009;Fonseca et al 2012), and cell cycle progression (Hwang and Madhani 2009) and can promote cancer Blank et al 2012;Johnsen 2012;. Several mechanisms have been proposed to underlie the ability of H2Bub1 to exert those diverse effects, including impact on higher-order chromatin organization (Fierz et al 2011), altered nucleosome stability (Chandrasekharan et al 2009), regulation of H2A-H2B dimer displacement (Pavri et al 2006), and modulation of the recruitment of specific factors to chromatin (Shema-Yaacoby et al 2013).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%